Thermoplastic resin film, laminate, and laminated glass
The use of a thermoplastic resin film with a specific metal salt of an organic acid in laminated glass production addresses the issue of clouding at high temperatures, ensuring the transparency and durability of laminated glass.
Patent Information
- Application Number
- JP2023204959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2025-06-16
AI Technical Summary
Laminated glass produced by low-temperature fusion using a soft interlayer film experiences clouding and appearance defects when exposed to high temperatures for extended periods.
A thermoplastic resin film with a multilayer structure, containing a thermoplastic resin layer with a thickness change of 80 μm or more upon compression creep testing, and incorporating a metal salt of an organic acid with a total carbon number of 5 or more, is used to prevent metal ion aggregation and clouding at high temperatures.
The proposed solution effectively suppresses clouding and maintains transparency of laminated glass even at high temperatures, ensuring long-term durability and performance.
Smart Images

Figure 2025089956000009 
Figure 2025089956000010 
Figure 2025089956000001
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin film, a laminate including the thermoplastic resin film, and laminated glass.
Background Art
[0002] Conventionally, laminated glass in which an intermediate film is interposed between two glass plates and integrated is widely known. The intermediate film is often formed of a plasticized polyvinyl acetal in which a plasticizer is blended with a polyvinyl acetal resin. Since laminated glass is safe because glass fragments are less likely to scatter even when it is damaged by an external impact, it is widely used as window glass for vehicles such as automobiles, airplanes, and buildings. For laminated glass, an intermediate film is disposed between two glass plates, and after a preliminary degassing process, it is heated and pressurized under conditions of a temperature of about 130 to 140°C and a pressure of about 1.3 MPa in an autoclave (ACV) process to bond the glass plate and the intermediate film for manufacturing. This is common.
[0003] An intermediate film for laminated glass usually contains an adhesion adjuster to adjust the adhesion to glass. As the adhesion adjuster, generally, magnesium acetate or potassium acetate is used. In addition to magnesium acetate and potassium acetate, metal carboxylates having a relatively large number of carbon atoms such as magnesium 2-ethylbutyrate and magnesium hexanoate may also be used (see, for example, Patent Documents 1 to 5).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Patent Document 3
Patent Document 4
[0005] Regarding laminated glass, in addition to an interlayer film between two glass sheets, it has been considered to dispose a functional film such as a heat-sensitive dimming film. Therefore, attempts have been made to bond laminated glass by low-temperature fusion without going through an autoclave process or by autoclaving at a low temperature. However, when attempting to produce laminated glass by low-temperature fusion using a general interlayer film for laminated glass, bonding cannot be properly performed, air remains, and there may be a problem that the transparency of the laminated glass obtained by bonding deteriorates. Therefore, when producing laminated glass by low-temperature fusion, it has been considered that a relatively soft interlayer film for laminated glass is used.
[0006] Incidentally, laminated glass is often used for a long period of time in a high-temperature state, such as being exposed to sunlight. However, laminated glass manufactured by low-temperature fusion using a soft interlayer film for laminated glass has a problem that clouding occurs and appearance defects occur when used for a long period of time in a high-temperature state.
[0007] Therefore, an object of the present invention is to provide a thermoplastic resin film suitable for low-temperature fusion and capable of suppressing the occurrence of clouding over time at high temperatures. Means for Solving the Problems
[0008] When the present inventors examined the factors causing clouding over time at high temperatures when using a soft thermoplastic resin film suitable for low-temperature fusion bonding, they found that metal ions such as magnesium ions constituting the metal salt used as an adhesion regulator aggregated and were unevenly distributed near the surface of the thermoplastic resin film, resulting in clouding. Therefore, as a result of further intensive studies, it was found that by using a metal salt of a specific organic acid, even a soft thermoplastic resin film can suppress the aggregation of metals at high temperatures and prevent the occurrence of clouding, and the following present invention was completed.
[0009] That is, the present invention provides the following [1] to
[10] . [1] A thermoplastic resin film having a single-layer structure or a multilayer structure, comprising at least a thermoplastic resin layer (A) containing a thermoplastic resin, when the thermoplastic resin film has a multilayer structure, at least one outermost layer is the thermoplastic resin layer (A), wherein the thermoplastic resin layer (A) has a thickness change amount of 80 μm or more when compressed by a compression creep test performed under the following conditions, and is a thermoplastic resin film containing a metal salt of an organic acid having a total carbon number of 5 or more. (Compression creep test conditions) A test sample having a diameter of 8 mm and a thickness of 700 to 900 μm prepared from the thermoplastic resin layer (A) is compressed for 5 minutes under the conditions of a load of 410 g and a temperature of 30°C, and then the thickness (T1) of the test sample is measured. Then, while maintaining a load of 410 g, the temperature is raised from 30°C to 90°C at a heating rate of 6°C / min. And after compressing for 5 minutes under the conditions of a load of 410 g and a temperature of 90°C, the thickness (T2) of the test sample is measured. The absolute value of the difference between the thickness (T1) and the thickness (T2) of the test sample is taken as the thickness change amount. [2] The thermoplastic resin film according to [1] above, wherein the carbon chain of the organic acid in the metal salt has a branched chain and the carbon number of the main chain of the carbon chain is 4 or more. [3] The thermoplastic resin film according to [1] or [2] above, wherein the carbon chain of the organic acid in the metal salt has a branched chain and the carbon number of the branched chain is 1 or more. [4] The thermoplastic resin film according to any one of [1] to [3] above, wherein in the thermoplastic resin layer (A), the content of the metal contained in the metal salt is 40 ppm or more. [5] The thermoplastic resin film according to any one of [1] to [4] above, wherein the thermoplastic resin layer (A) does not contain a metal salt of an organic acid having 1 to 4 carbon atoms in total, or contains a metal salt of an organic acid having 1 to 4 carbon atoms in total in an amount less than 40 ppm in terms of the metal amount. [6] The thermoplastic resin film according to any one of [1] to [5] above, wherein the thermoplastic resin is a polyvinyl acetal resin. [7] The thermoplastic resin film according to [6] above, wherein the polyvinyl acetal resin is a polyvinyl acetal resin aged at 30°C or higher and 65°C or lower for 75 minutes or more and 180 minutes or less. [8] The thermoplastic resin film according to any one of [1] to [7] above, which is an interlayer film for laminated glass. [9] A laminate comprising the thermoplastic resin film according to any one of [1] to [7] above and at least one of a functional layer and a transparent substrate.
[10] A laminated glass comprising the thermoplastic resin film according to any one of [1] to [7] above and a pair of glass members, wherein the thermoplastic resin film is disposed between the pair of glass members. [Advantages of the Invention]
[0010] According to the present invention, it is possible to provide a thermoplastic resin film that is suitable for low-temperature fusion bonding and can suppress the occurrence of cloudiness over time at high temperatures. [Brief Description of the Drawings]
[0011]
Figure 1
Figure 2
[0012] [Thermoplastic Resin Film] The thermoplastic resin film of the present invention has a single-layer structure or a multilayer structure, and at least includes a thermoplastic resin layer (A) containing a thermoplastic resin (hereinafter sometimes referred to as "thermoplastic resin (a)"). When the thermoplastic resin film has a multilayer structure, at least one outermost layer is the thermoplastic resin layer (A). And the amount of thickness change when the thermoplastic resin layer (A) is compressed by a compression creep test performed under the following conditions is 80 μm or more.
[0013] (Compression Creep Test) First, a test sample with a diameter of 8 mm and a thickness of 700 to 900 μm (for example, 800 μm) is prepared from the thermoplastic resin layer (A). Next, after the test sample is compressed for 5 minutes under the conditions of a load of 410 g and a temperature of 30°C, the thickness (T1) of the test sample is measured. Then, while maintaining a load of 410 g, the temperature is raised from 30°C to 90°C at a heating rate of 6°C / min. And after compressing for 5 minutes under the conditions of a load of 410 g and a temperature of 90°C, the thickness (T2) of the test sample is measured. The absolute value of the difference between the thickness (T1) and the thickness (T2) of the test sample is taken as the amount of thickness change.
[0014] In addition, when the thickness of the thermoplastic resin layer (A) is less than 700 μm, the test sample may be prepared by stacking two or more thermoplastic resin layers, appropriately heat-pressing and bonding them, and adjusting the thickness to 700 to 900 μm by pressing or the like, and then cutting or the like to form a cylindrical shape with a diameter of 8 mm. Also, when the thickness of the thermoplastic resin layer (A) exceeds 900 μm, the test sample may be prepared by adjusting the thickness to 900 μm by heat-pressing or the like as necessary, and then cutting or the like to form a cylindrical shape with a diameter of 8 mm. In addition, when the thermoplastic resin film has a multilayer structure, the thermoplastic resin layer (A) is taken out by peeling the thermoplastic resin layer (A) from other layers. Also, when there are irregularities such as embossing on the surface of the test sample, the test sample may be appropriately adjusted to have a flat surface by heat-pressing or the like, and then the test sample may be manufactured by cutting or the like to form a cylindrical shape with a diameter of 8 mm.
[0015] When the amount of thickness change of the thermoplastic resin layer (A) is less than 80 μm, for example, when a thermoplastic resin film is pressure-bonded to other members such as a transparent substrate or a functional layer by an autoclave or means other than an autoclave at a low temperature to produce a laminate, air may remain between the thermoplastic resin film and the other members, and the transparency of the laminate such as laminated glass may deteriorate. Therefore, it becomes impossible to appropriately produce a laminate such as laminated glass by low-temperature fusion or the like. From such a viewpoint, the amount of thickness change of the thermoplastic resin layer (A) is preferably 85 μm or more, more preferably 90 μm or more, still more preferably 100 μm or more, and even more preferably 110 μm or more. When the amount of thickness change becomes large in this way, the amount of air remaining during pressure bonding can be further reduced. The amount of thickness change of the thermoplastic resin layer (A) is, for example, 450 μm or less, preferably 350 μm or less, more preferably 250 μm or less, and still more preferably 150 μm or less. When the amount of thickness change is set to a certain value or less, it becomes easier to improve the high-temperature heat resistance of the thermoplastic resin film and the like. Also, foaming is less likely to occur at the ends of the laminate such as laminated glass during pressure bonding.
[0016] The amount of thickness change can be adjusted, for example, by the thermoplastic resin (a) contained in the thermoplastic resin layer (A). For example, when using a polyvinyl acetal resin, it can also be adjusted by the production conditions and the like during the production of the polyvinyl acetal resin. Specifically, as described later, the amount of thickness change can be adjusted by the aging temperature in the aging process performed when producing the polyvinyl acetal resin. It can also be adjusted by the molecular weight of the thermoplastic resin (a). For example, when using a low-molecular-weight thermoplastic resin (a), the amount of thickness change tends to increase. Furthermore, the amount of thickness change can also be adjusted by the amount and type of the plasticizer. For the thermoplastic resin layer (A), for example, when the amount of the plasticizer is increased, the amount of thickness change tends to increase.
[0017] [Weight average molecular weight] The weight average molecular weight (Mw) of the thermoplastic resin (a) in the thermoplastic resin layer (A) is, for example, 180,000 or more and 350,000 or less, preferably 220,000 or more and 310,000 or less, more preferably 240,000 or more and 300,000 or less. By setting the weight average molecular weight of the thermoplastic resin (a) to a certain value or more, it becomes difficult for bubbles to generate in the thermoplastic resin film, and the high-temperature heat resistance of the thermoplastic resin film becomes good. Also, by setting the weight average molecular weight to a certain value or less, it becomes soft and it becomes easier to increase the amount of thickness change during compression creep.
[0018] [Molecular weight distribution] The molecular weight distribution represented by the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) in the thermoplastic resin (a) of the thermoplastic resin layer (A) is, for example, 1.0 or more and 3.5 or less. By lowering Mw / Mn, the high-temperature heat resistance becomes good, and it is possible to prevent the generation of bubbles due to use in a high-temperature environment. From such a viewpoint, the molecular weight distribution (Mw / Mn) is preferably 1.0 or more and 2.5 or less, more preferably 1.1 or more and 2.3 or less, and even more preferably 1.3 or more and 2.0 or less. Also, when the molecular weight distribution (Mw / Mn) is increased, the amount of low molecular weight components increases, and it becomes easier to increase the amount of thickness change during compression creep. Therefore, by adjusting the molecular weight distribution, the amount of thickness change during compression creep can be adjusted within the above-mentioned predetermined range. From such a viewpoint, the molecular weight distribution is, for example, preferably greater than 2.5, preferably 2.6 or more and 3.5 or less, more preferably 2.8 or less and 3.5 or less. Note that the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the thermoplastic resin (a) in the thermoplastic resin layer (A) are measured by gel permeation chromatography.
[0019] Examples of the thermoplastic resin (a) used in the thermoplastic resin layer (A) of the present invention include (meth)acrylic resins, polyvinyl acetal resins, polyvinyl alcohol resins (PVA), polyurethane resins (PU), ethylene-vinyl acetate copolymer resins (EVA), saponified ethylene-vinyl acetate copolymers (EVOH), ethylene-methacrylic acid copolymer resins, ionomer resins, isobutylene resins, styrene-isoprene copolymer resins, styrene-butadiene copolymer resins, etc. The thermoplastic resin may be used alone or in combination of two or more.
[0020] Among the above, from the viewpoint of achieving both moisture and heat resistance and impact resistance, the thermoplastic resin (a) is preferably a polyvinyl acetal resin, a polyurethane resin (PU), an ethylene-vinyl acetate copolymer resin (EVA), a saponified ethylene-vinyl acetate copolymer (EVOH), an ethylene-methacrylic acid copolymer resin, an ionomer resin, an isobutylene resin, a styrene-isoprene copolymer resin, or a styrene-butadiene copolymer resin. Further, among the above, the polyvinyl acetal resin is more preferable as the thermoplastic resin. By using the polyvinyl acetal resin, it is easy to obtain excellent impact resistance. Also, it becomes easy to adjust the amount of thickness change within the above-mentioned predetermined range. Furthermore, it becomes easy to improve the adhesion to various resin materials and inorganic glasses. Hereinafter, the polyvinyl acetal resin used for the thermoplastic resin (a) will be described in detail.
[0021] (Polyvinyl Acetal Resin) The polyvinyl acetal resin is not particularly limited as long as it is a polyvinyl acetal resin obtained by acetalizing polyvinyl alcohol (PVA) with an aldehyde. The above aldehyde is not particularly limited, but generally, aldehydes having 1 to 10 carbon atoms are preferably used. The aldehydes having 1 to 10 carbon atoms are not particularly limited. For example, n-butyl aldehyde, isobutyl aldehyde, n-valeraldehyde, 2-ethylbutyl aldehyde, n-hexyl aldehyde, n-octyl aldehyde, n-nonyl aldehyde, n-decyl aldehyde, formaldehyde, acetaldehyde, benzaldehyde, etc. may be mentioned. These aldehydes may be used alone or in combination of two or more. Among the above, n-butyl aldehyde, n-hexyl aldehyde, and n-valeraldehyde are preferred, and n-butyl aldehyde is more preferred. Therefore, as the polyvinyl acetal resin, polyvinyl butyral resin is suitable.
[0022] Polyvinyl alcohol (PVA), which is a raw material of the polyvinyl acetal resin, can be obtained, for example, by saponifying a polyvinyl ester such as polyvinyl acetate. The saponification degree of polyvinyl alcohol is generally 70 to 99.9 mol%. The average degree of polymerization of PVA is preferably 200 or more, more preferably 500 or more, still more preferably 750 or more, and even more preferably 1200 or more. When the average degree of polymerization is at least the above lower limit, the penetration resistance of the laminated glass becomes high when used for laminated glass. Also, the average degree of polymerization of PVA is preferably 5000 or less, more preferably 3500 or less, still more preferably 3000 or less, and even more preferably 2000 or less. In addition, the average degree of polymerization of polyvinyl alcohol is determined by a method in accordance with JIS K6726 "Test Methods for Polyvinyl Alcohol". When two or more kinds of polyvinyl alcohol are used as raw materials, the average degree of polymerization of polyvinyl alcohol may be estimated by calculation from the average degree of polymerization of each polyvinyl alcohol.
[0023] For the polyvinyl alcohol used as a raw material of the polyvinyl acetal resin, two or more kinds of polyvinyl alcohol having different average polymerization degrees may be used. In this case, a mixture of two or more kinds of polyvinyl alcohol may be used as a raw material to produce a polyvinyl acetal resin by the production method described later, or it may be produced by different production methods. When using two or more kinds of polyvinyl alcohol, for example, it is preferable to use a first polyvinyl alcohol having an average polymerization degree of 1500 or more and a second polyvinyl alcohol having an average polymerization degree of 1200 or less. By using two or more kinds of polyvinyl alcohol having different average polymerization degrees, it becomes easier to increase the amount of thickness change. The average polymerization degree of the first polyvinyl alcohol is preferably 1500 or more and 3500 or less, more preferably 1600 or more and 2500 or less, and still more preferably 1600 or more and 2000 or less. Also, the average polymerization degree of the second polyvinyl alcohol is preferably 200 or more and 1200 or less, more preferably 300 or more and 900 or less, and still more preferably 400 or more and 850 or less.
[0024] When using the first and second polyvinyl alcohols, the blending ratio of the first polyvinyl alcohol and the second polyvinyl alcohol is not particularly limited, but the blending amount of the second polyvinyl alcohol with respect to the total amount of the first and second polyvinyl alcohols may be, for example, 1% by mass or more and 80% by mass or less. Increasing the blending amount of the second polyvinyl alcohol makes it easier to increase the amount of thickness change during compression creep, while decreasing the blending amount makes it easier to improve the high-temperature heat resistance. From the viewpoint of improving the high-temperature heat resistance and increasing the amount of thickness change, the blending amount of the second polyvinyl alcohol is preferably 1% by mass or more and 50% by mass or less, more preferably 3% by mass or more and 40% by mass or less, still more preferably 5% by mass or more and 30% by mass or less, and even more preferably 10% by mass or more and 25% by mass or less. In addition, the blending amount of the second polyvinyl alcohol is preferably 20% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 75% by mass or less, and even more preferably 40% by mass or more and 70% by mass or less in order to increase the molecular weight distribution and adjust the amount of thickness change during compression creep within the above-mentioned predetermined range according to the molecular weight distribution.
[0025] The amount of hydroxyl groups in the polyvinyl acetal resin is preferably 15 mol% or more and preferably 38 mol% or less. By setting the amount of hydroxyl groups to 15 mol% or more, the adhesiveness tends to be good, and when used for laminated glass, the penetration resistance of the laminated glass and the like tend to be good. Also, by setting the amount of hydroxyl groups to 38 mol% or less, flexibility is easily ensured, and it is possible to prevent the laminate such as laminated glass from becoming too hard or the amount of thickness change from becoming too low. In addition, by adjusting the amount of hydroxyl groups within the above range, the generation of bubbles due to use in a high-temperature environment can be further suppressed, and the high-temperature heat resistance of the thermoplastic resin film can be further improved. The above amount of hydroxyl groups is more preferably 20 mol% or more, and even more preferably 25 mol% or more. Also, the above amount of hydroxyl groups is more preferably 35% or less, and even more preferably 33 mol% or less. When using polyvinyl butyral resin as the polyvinyl acetal resin, from the same viewpoint, the amount of hydroxyl groups is 15 mol% or more, preferably 38 mol% or less, more preferably 20 mol% or more, even more preferably 25 mol% or more, more preferably 35 mol% or less, and even more preferably 33 mol% or less. The amount of hydroxyl groups in the polyvinyl acetal resin is a value obtained by dividing the amount of ethylene groups to which hydroxyl groups are bonded by the total amount of ethylene groups in the main chain and expressing the mole fraction as a percentage. The amount of ethylene groups to which the above hydroxyl groups are bonded can be measured according to the procedure described in the examples.
[0026] The degree of acetylation of the polyvinyl acetal resin is preferably 30 mol% or less, more preferably 20 mol% or less, still more preferably 10 mol% or less, and even more preferably 2 mol% or less. When the degree of acetylation is within the above upper limit, the moisture resistance of the polymer film increases. Also, the degree of acetylation is not particularly limited, but is preferably 0.01 mol% or more, and more preferably 0.1 mol% or more. The degree of acetylation is a value obtained by dividing the amount of ethylene groups to which acetyl groups are bonded by the total amount of ethylene groups in the main chain and expressing the molar fraction as a percentage. The amount of ethylene groups to which the acetyl groups are bonded can be measured according to the procedure described in the examples.
[0027] The degree of acetalization of the polyvinyl acetal resin is preferably 47 mol% or more, and also preferably 85 mol% or less. The degree of acetalization is more preferably 55 mol% or more, still more preferably 60 mol% or more, and also more preferably 80 mol% or less, still more preferably 75 mol% or less. Note that when the acetal group is a butyral group and the polyvinyl acetal resin (A) is a polyvinyl butyral resin, the degree of acetalization means the degree of butyralization.
[0028] The degree of acetalization is a value obtained by dividing the value obtained by subtracting the amount of ethylene groups to which hydroxyl groups are bonded and the amount of ethylene groups to which acetyl groups are bonded from the total amount of ethylene groups in the main chain by the total amount of ethylene groups in the main chain, and expressing the molar fraction as a percentage. The degree of acetalization (degree of butyralization) may be calculated based on the amount of ethylene groups to which hydroxyl groups are bonded and the amount of ethylene groups to which acetyl groups are bonded obtained according to the procedure described in the examples.
[0029] The polyvinyl acetal resin may be an unmodified polyvinyl acetal resin, or may be a modified polyvinyl acetal resin. The modified polyvinyl acetal resin has a structure other than an acetal group, a hydroxyl group, and an acetyl group (modified group), and preferably has the modified group in the side chain. Examples of the modified group include those having a polyalkylene oxide structure in the side chain and those having an alkyl group other than an acetal group and an acetyl group (for example, having about 2 to 30 carbon atoms) in the side chain. The amount of modification is not particularly limited, but is, for example, about 0.1 mol% or more and about 10 mol%. The amount of modification represents the ratio of the functional group to all the vinyl monomer units constituting the polyvinyl acetal resin. In the thermoplastic resin layer (A), the polyvinyl acetal resin may be used alone or in combination of two or more.
[0030] When the thermoplastic resin layer (A) uses a polyvinyl acetal resin as the thermoplastic resin (a), as long as the effects of the present invention are achieved, it may contain a thermoplastic resin other than the polyvinyl acetal resin. The thermoplastic resin other than the polyvinyl acetal resin is as described above. However, in the thermoplastic resin layer (A), the polyvinyl acetal resin is preferably the main component. Specifically, the content of the polyvinyl acetal resin is, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass based on the total amount of the thermoplastic resin (a) contained in the thermoplastic resin layer (A). Therefore, the thermoplastic resin (a) contained in the thermoplastic resin layer (A) of the present invention may consist only of the polyvinyl acetal resin.
[0031] (Method for producing polyvinyl acetal resin) The polyvinyl acetal resin is preferably produced by a production method including a mixing step of mixing the above polyvinyl alcohol and the above aldehyde, and an aging step of aging the mixture obtained in the mixing step.
[0032] In the mixing process, it is advisable to mix polyvinyl alcohol and aldehyde according to the conventional method. Further, a catalyst such as an acid catalyst for promoting the acetalization reaction may be added in addition to polyvinyl alcohol and aldehyde. For example, aldehyde may be added to a mixture obtained by adding an acid catalyst to polyvinyl alcohol under low-temperature conditions of about 0 to 40°C. Further, when two or more kinds of polyvinyl alcohol are used in combination (for example, when two or more kinds of polyvinyl alcohol having different molecular weights are used), it is advisable to mix two or more kinds of polyvinyl alcohol with aldehyde.
[0033] The aging process is not particularly limited. For example, a catalyst such as an acid catalyst may be added to the mixture (reaction mixture) obtained by the above mixing process, heated to the aging temperature, and held at the aging temperature for a certain period of time. In this production method, in the mixing process and the aging process, acetalization of polyvinyl alcohol proceeds to obtain a polyvinyl acetal resin. After the reaction mixture is held at the above aging temperature for a certain period of time, it may be appropriately cooled and then neutralized, and then washed with water and dried as necessary.
[0034] Examples of the acid catalyst added in the above mixing process and aging process include inorganic acids such as hydrochloric acid, nitric acid, phosphoric acid, boric acid, and sulfuric acid. Further, in the aging process, the concentration of the acid catalyst is preferably adjusted to a concentration of, for example, 0.5% by mass or more and 5% by mass or less, preferably 1% by mass or more and 2.5% by mass or less. The aging temperature in the aging process is preferably carried out at a relatively low temperature. For example, it is 30°C or higher and 65°C or lower, preferably 40°C or higher and 60°C or lower, more preferably 45°C or higher and 57°C or lower. Further, the time (aging time) of holding at the above aging temperature may be longer than a certain time. For example, it is 75 minutes or more and 180 minutes or less, preferably 90 minutes or more and 150 minutes or less, more preferably 100 minutes or more and 140 minutes or less. When the aging temperature and the aging time are within the above desired ranges, it is presumed that the hydroxyl groups are likely to be uniformly distributed in the polyvinyl acetal resin molecule. As a result, the polyvinyl acetal resin becomes soft and the amount of thickness change can be increased.
[0035] (Plasticizer) The thermoplastic resin layer (A) preferably contains a plasticizer. By containing a plasticizer, the thermoplastic resin layer (A) becomes flexible, and the adhesiveness of the thermoplastic resin layer (A) to various members and the penetration resistance can be improved. In addition, it becomes easier to increase the amount of thickness change.
[0036] Examples of the plasticizer include organic ester plasticizers, organic phosphorus plasticizers such as organic phosphate plasticizers and organic phosphite plasticizers, organic ether plasticizers such as polyalkylene glycol plasticizers, and alcohol plasticizers. The plasticizer may be used alone or in combination of two or more. Among those described above, organic ester plasticizers and organic ether plasticizers are preferred.
[0037] Preferred organic ester plasticizers include monobasic organic acid esters and polybasic organic acid esters. Examples of the monobasic organic acid ester include esters of glycol and monobasic organic acid. Examples of the glycol include polyalkylene glycols in which each alkylene unit has 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms, and the repeating number of the alkylene unit is 2 to 10, preferably 2 to 4. Further, the glycol may be a monoalkylene glycol having 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms (that is, the repeating unit is 1). Specific examples of the glycol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and butylene glycol. Examples of the monobasic organic acid include organic acids having 3 to 10 carbon atoms, and specifically include butyric acid, isobutyric acid, caproic acid, 2-ethylbutyric acid, heptanoic acid, n-octylic acid, 2-ethylhexanoic acid, n-nonanoic acid, and decylic acid.
[0038] Specific monobasic organic acids include triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol dicaprylate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, tetraethylene glycol di-2-ethylhexanoate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylpentanoate, tetraethylene glycol di-2-ethylbutyrate, diethylene glycol dicaprylate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, triethylene glycol di-2-ethylbutyrate, ethylene glycol di-2-ethylbutyrate, 1,2-propylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, 1,4-butylene glycol di-2-ethylbutyrate, 1,2-butylene glycol di-2-ethylbutyrate, and the like.
[0039] In addition, examples of polybasic organic acid esters include ester compounds of dibasic organic acids having 4 to 12 carbon atoms, such as adipic acid, sebacic acid, and azelaic acid, and alcohols having 4 to 10 carbon atoms. The alcohol having 4 to 10 carbon atoms may be linear, may have a branched structure, or may have a cyclic structure. Specifically, examples include dibutyl sebacate, dioctyl azelate, dihexyl adipate, dioctyl adipate, hexyl cyclohexyl adipate, diisononyl adipate, heptyl nonyl adipate, dibutyl carbitol adipate, mixed adipic acid esters, and the like. Also, oil-modified sebacic acid alkyds and the like may be used. Examples of mixed adipic acid esters include adipic acid esters prepared from two or more alcohols selected from alkyl alcohols having 4 to 9 carbon atoms and cyclic alcohols having 4 to 9 carbon atoms.
[0040] The organic ester plasticizer is not limited to the complete esters of the above-mentioned esters, and partial esters may also be used. For example, it may be a partial ester of glycol and a monobasic organic acid, or a partial ester of a dibasic organic acid and an alcohol. Specifically, triethylene glycol-mono-2-ethylhexanoate and the like can be mentioned. Furthermore, it may be a partial ester of a trivalent or higher alcohol such as glycerin and a monobasic organic acid. Examples of the monobasic organic acid include monobasic organic acids having 3 to 24 carbon atoms, preferably 6 to 18 carbon atoms. Specific examples of the partial ester of a trivalent or higher alcohol and a monobasic organic acid include mono- or diesters of glycerin and stearic acid, mono- or diesters of glycerin and 2-ethylhexanoic acid, and the like. Among the above-mentioned organic ester plasticizers, triethylene glycol-di-2-ethylhexanoate (3GO) is particularly preferably used.
[0041] Examples of the organic phosphorus plasticizer include phosphate esters such as tributoxyethyl phosphate, isodecyl phenyl phosphate, and triisopropyl phosphate.
[0042] Examples of the polyalkylene glycol plasticizer include polyoxyalkylene compounds having a polyoxyalkylene structure. Specifically, polyhydric alcohol compounds such as glycol, ester compounds of glycol and a monobasic or polybasic organic acid, ether compounds of a monovalent or polyhydric alcohol and polyoxyalkylene, and the like can be mentioned. Here, examples of the glycol include polyoxyalkylene glycol and its derivatives. Examples of the polyoxyalkylene include polyoxyethylene, polyoxypropylene, polyoxybutylene, random copolymers or block copolymers thereof, and the like. The polyoxyalkylene compound may be a polyhydric alcohol compound, an ester compound, an ether compound, or other compounds as described above.
[0043] Examples of the polyoxyalkylene compound include polyoxyalkylene or its derivatives. More specifically, examples include polyoxyalkylene glycols composed of the above polyoxyalkylene, ether compounds of polyoxyalkylene and polyhydric alcohols, etc. All of these may have hydroxyl groups at all terminals, but a part or all of the terminal hydroxyl groups may be derivatives in which a hydrogen atom is substituted with an alkyl group or an acyl group. The carbon number of the alkyl group and the acyl group is not particularly limited, but may be about 1 to 8, preferably 1 to 4.
[0044] Examples of the polyoxyalkylene glycol include polyoxyethylene polyoxypropylene glycols such as polyethylene glycol (polyoxyethylene glycol), polypropylene glycol (polyoxypropylene glycol), poly(ethylene oxide / propylene oxide) block copolymer, poly(ethylene oxide / propylene oxide) random copolymer, and polyoxybutylene glycols such as polytetramethylene glycol.
[0045] Examples of ether compounds of polyoxyalkylene and polyhydric alcohol include polyhydric alcohols such as glycerol, diglycerol, trimethylolpropane, erythritol, pentaerythritol, and bisphenol A, and ether compounds of polyoxyalkylene. Specifically, polyoxyethylene glyceryl ether, polyoxypropylene glyceryl ether, polyoxyethylene diglyceryl ether, polyoxypropylene diglyceryl ether, polyoxyalkylene pentaerythritol ether, etc. can be mentioned. Further, as derivatives in which part or all of the hydrogen atoms of the terminal hydroxyl group are substituted with an alkyl group or an acyl group, there are mentioned the above polyoxyalkylene glycols and derivatives in which part or all of the hydrogen atoms of the terminal hydroxyl group of the ether compound are substituted with an alkyl group or an acyl group. Specifically, polyoxyethylene glycol monomethyl ether, polyoxyethylene glycol dimethyl ether, polyoxypropylene glycol monomethyl ether, polyoxypropylene glycol dimethyl ether, polyoxyethylene polyoxypropylene glycol monomethyl ether, polyoxyethylene polyoxypropylene glycol dimethyl ether, polyoxyethylene glycol monobutyl ether, polyoxypropylene glycol monobutyl ether, polyoxyethylene polyoxypropylene monobutyl ether, etc. can be mentioned.
[0046] Among the above, polyoxyalkylene compounds having a polyoxyethylene, polyoxypropylene, or polyoxyethylene polyoxypropylene structure are preferred, and among them, those having a polyoxypropylene or polyoxyethylene polyoxypropylene structure are more preferred. Specifically, polyoxyethylene polyoxypropylene glycol, polyoxypropylene glyceryl ether, polyoxypropylene diglyceryl ether, or derivatives in which part of the hydrogen atoms of their terminal hydroxyl groups are substituted with an alkyl group are preferred.
[0047] Examples of the alcohol-based plasticizer include various polyhydric alcohols such as butanediol, hexanediol, trimethylolpropane, and pentaerythritol. Among these, trimethylolpropane is preferred.
[0048] The above plasticizers can be used alone or in combination of two or more. Among the above plasticizers, triethylene glycol-di-2-ethylhexanoate (3GO), polyoxyethylene polyoxypropylene glycol, polyoxypropylene glyceryl ether, polyoxypropylene diglyceryl ether, or derivatives in which some of the hydrogen atoms of the terminal hydroxyl groups are substituted with alkyl groups are preferred, and triethylene glycol-di-2-ethylhexanoate (3GO) is more preferred.
[0049] The content of the plasticizer in the thermoplastic resin layer (A) is not particularly limited, but is preferably 10 parts by mass or more and 100 parts by mass or less with respect to 100 parts by mass of the thermoplastic resin (a). When the content of the plasticizer is 10 parts by mass or more, the thermoplastic resin layer (A) becomes moderately flexible, and the adhesiveness of the thermoplastic resin layer (A) and the penetration resistance of the laminated glass are improved. Furthermore, the amount of thickness change is also easily increased. On the other hand, when the content of the plasticizer is 100 parts by mass or less, separation of the plasticizer from the thermoplastic resin layer (A) is prevented. Also, it is possible to prevent the amount of thickness change from becoming too large. The above content of the plasticizer is more preferably 15 parts by mass or more, further preferably 30 parts by mass or more, still more preferably 35 parts by mass or more, and more preferably 70 parts by mass or less, further preferably 60 parts by mass or less, still more preferably 50 parts by mass or less.
[0050] (Metal salt of organic acid) The thermoplastic resin layer (A) contains a metal salt of an organic acid having 5 or more carbon atoms in total. The metal salt of an organic acid having 5 or more carbon atoms in total functions as a so-called adhesion adjuster, and by containing the metal salt of an organic acid having 5 or more carbon atoms in total, the thermoplastic resin layer (A) can adjust the adhesion to other members such as glass within an appropriate range. Further, the thermoplastic resin layer (A) contains a metal salt of an organic acid having 5 or more carbon atoms in total, so that the amount of thickness change is 80 μm or more, and even though it is soft, it is possible to prevent cloudiness from occurring when heated to a high temperature without aggregation of metal ions constituting the metal salt. The principle is not clear, but in the case of a metal salt of an organic acid, since the carbon number of the organic acid is large, the hydrophobic part becomes large, so the hydrophobic part is compatible with the thermoplastic resin (a) and is easily uniformly dispersed in the resin layer (A). As a result, it is presumed that since metal ions are less likely to condense, cloudiness over time during high-temperature heating is suppressed even if the thermoplastic resin (a) is soft.
[0051] From the viewpoint of more effectively preventing aggregation of metal ions, the organic acid constituting the metal salt of the organic acid preferably has 6 or more carbon atoms in total. Further, the organic acid may have, for example, 18 or less carbon atoms in total, preferably 10 or less, more preferably 8 or less. The organic acid is preferably a carboxylic acid, more preferably an aliphatic carboxylic acid, and even more preferably a saturated aliphatic carboxylic acid.
[0052] Further, the organic acid preferably has a branched carbon chain. A metal salt of an organic acid having a branched chain has higher hydrophobicity and can more effectively prevent aggregation of metal ions. From the viewpoint of preventing aggregation of the metal and suppressing cloudiness over time during high-temperature heating, the main chain of the carbon chain having a branched chain is preferably 4 or more. Further, the main chain of the carbon chain having a branched chain is preferably 8 or less, more preferably 6 or less. When the organic acid has a branched chain, the number of carbon atoms in the branched chain is preferably 1 or more, more preferably 2 or more, from the viewpoint of preventing aggregation of the metal and suppressing cloudiness over time during high-temperature heating. Further, the number of carbon atoms in the branched chain is preferably 4 or less, more preferably 3 or less, and most preferably 2. Note that the carbon chain of the organic acid refers to the part where carbon atoms are continuous in the organic acid, and the carbon atoms that bind to molecules other than hydrogen atoms and carbon atoms such as carboxyl groups are also included in the carbon chain. Also, the main chain is the straight carbon chain part with the largest number of carbon atoms among the carbon chains, and the branched chain is the part other than the main chain.
[0053] Specific examples of the organic acid include 2-ethylbutyric acid, 2-ethylhexanoic acid, n-octanoic acid, n-heptanoic acid, n-hexanoic acid, n-pentanoic acid, etc. Among these, 2-ethylbutyric acid, 2-ethylhexanoic acid, n-octanoic acid, and n-pentanoic acid are preferred, and among them, 2-ethylbutyric acid is more preferred. The metal constituting the metal salt is preferably magnesium, potassium, or calcium, and more preferably magnesium. Specific examples of the preferred metal salts of organic acids include magnesium 2-ethylbutyrate, magnesium 2-ethylhexanoate, magnesium n-octanoate, magnesium n-heptanoate, magnesium n-hexanoate, magnesium n-pentanoate. Among these, magnesium 2-ethylbutyrate, magnesium 2-ethylhexanoate, magnesium n-octanoate, and magnesium n-pentanoate are preferred, and particularly magnesium 2-ethylbutyrate is more preferred.
[0054] In the thermoplastic resin layer (A), the content of the metal contained in the metal salt of the organic acid having 5 or more carbon atoms in total is preferably 40 ppm or more on a mass basis. By setting it to 40 ppm or more, it becomes easier to adjust the adhesive force to other members such as glass within an appropriate range. The content of the above metal is more preferably 50 ppm or more, and still more preferably 60 ppm or more. Also, the content of the above metal is preferably 150 ppm or less, more preferably 100 ppm or less, and still more preferably 90 ppm or less on a mass basis. By setting the content of the above metal to be below the above upper limit value, the moisture resistance becomes good, and it is possible to prevent the occurrence of cloudiness due to water absorption or the like.
[0055] The thermoplastic resin layer (A) preferably does not contain a metal salt of an organic acid having 1 to 4 carbon atoms in total, or contains a metal salt of an organic acid having 1 to 4 carbon atoms in total in an amount of less than 40 ppm in terms of the metal content. By not containing or containing only a small amount of a metal of an organic acid having a small total carbon number in the thermoplastic resin layer (A), aggregation of the metal is less likely to occur, and generation of cloudiness over time at high temperatures is more easily suppressed. From the viewpoint of making it even easier to suppress the generation of cloudiness over time at high temperatures, the thermoplastic resin layer (A) preferably does not contain a metal salt of an organic acid having 1 to 4 carbon atoms in total, or even if it contains such a metal salt, the content thereof is less than 20 ppm in terms of the metal content. More preferably, the thermoplastic resin layer (A) does not contain a metal salt of an organic acid having 1 to 4 carbon atoms in total, or even if it contains such a metal salt, the content thereof is less than 10 ppm in terms of the metal content. Most preferably, the thermoplastic resin layer (A) does not contain a metal salt of an organic acid having 1 to 4 carbon atoms in total.
[0056] (Other additives) In addition to the plasticizer and the metal salt of the organic acid, the thermoplastic resin layer (A) may appropriately contain known additives used in combination with the thermoplastic resin (a). That is, the thermoplastic resin layer (A) may be composed of the thermoplastic resin (a) such as a polyvinyl acetal resin and a metal salt of an organic acid, or the thermoplastic resin (a), a metal salt of an organic acid, and a plasticizer. However, in addition to these, it may contain additives other than the plasticizer and the metal salt of the organic acid that are blended as necessary. Specific examples of the additives other than the plasticizer and the metal salt of the organic acid include ultraviolet absorbers, infrared absorbers, antioxidants, light stabilizers, colorants (pigments or dyes), fluorescent brighteners, crystal nucleating agents, and the like.
[0057] <Colorant> The above thermoplastic resin layer (A) may or may not contain a colorant. By using the above colorant, the laminated glass can be satisfactorily colored to a desired color tone. Only one kind of the above colorant may be used, or two or more kinds may be used in combination. The thermoplastic resin layer (A) may contain only one kind of the colorant, two or more kinds, three or more kinds, ten or less kinds, or five or less kinds of the colorant.
[0058] Examples of the coloring agent include pigments and dyes. The coloring agent may be a pigment, a dye, or both. There are also coloring agents classified as both pigments and dyes.
[0059] Pigment: The coloring agent may contain a pigment or may be a pigment. The thermoplastic resin layer (A) may or may not contain a pigment. Only one type of the pigment may be used, or two or more types may be used in combination. The thermoplastic resin layer (A) may contain only one type of pigment, two or more types of pigments, three or more types of pigments, ten or fewer types of pigments, or five or fewer types of pigments.
[0060] Examples of the pigment include perylene compounds, threne compounds, quinacridone compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, perinone compounds, phthalocyanine compounds, indanthrene compounds, indigo compounds, isoindolinone compounds, nickel complex compounds, methine compounds, azomethine compounds, dioxazines, azo compounds, and carbon black.
[0061] When the thermoplastic resin layer (A) contains a pigment, the content of the pigment in 100% by mass of the thermoplastic resin layer (A) is preferably 0.0001% by mass or more, more preferably 0.01% by mass or more, still more preferably 0.02% by mass or more, preferably 0.15% by mass or less, and more preferably 0.12% by mass or less. When the content of the pigment is within the above lower limit and upper limit, the effects of the present invention can be more effectively exerted.
[0062] Dye: The above colorant may contain a dye or may be a dye. The above thermoplastic resin layer (A) may or may not contain a dye. Only one kind of the above dye may be used, or two or more kinds may be used in combination. The above thermoplastic resin layer (A) may contain only one kind of dye, may contain two or more kinds, may contain three or more kinds, may contain ten or less kinds, or may contain five or less kinds.
[0063] Examples of the above dye include perylene compounds, threne compounds, quinacridone compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, perinone compounds, phthalocyanine compounds, indanthrene compounds, indigo compounds, isoindolinone compounds, nickel complex compounds, methine compounds, azomethine compounds, dioxazines, and azo compounds.
[0064] When the above thermoplastic resin layer (A) contains a dye, the content of the above dye in 100% by mass of the above thermoplastic resin layer (A) is preferably 0.00001% by mass or more, more preferably 0.0001% by mass or more, still more preferably 0.001% by mass or more, preferably less than 0.015% by mass, and more preferably 0.01% by mass or less. When the content of the above dye is not less than the above lower limit and not more than (or less than) the above upper limit, the effects of the present invention can be more effectively exerted.
[0065] When the above thermoplastic resin layer (A) contains a colorant, the content of the above colorant in 100% by mass of the above thermoplastic resin layer (A) is preferably 0.00001% by mass or more, more preferably 0.0001% by mass or more, still more preferably 0.001% by mass or more, preferably 0.15% by mass or less, and more preferably 0.12% by mass or less. When the content of the above colorant is not less than the above lower limit and not more than (or less than) the above upper limit, the effects of the present invention can be more effectively exerted.
[0066] The thickness of the thermoplastic resin film is not particularly limited, but for example, it is 100 μm or more and 2000 μm or less, preferably 200 μm or more and 1300 μm or less, more preferably 300 μm or more and 1000 μm or less. When the thickness of the thermoplastic resin film is at least the above lower limit value, the impact resistance can be enhanced, and it becomes easier to ensure the adhesiveness to a transparent member such as a glass plate or a functional layer. On the other hand, by setting it to be at most the above upper limit value, it is possible to prevent the thickness of the thermoplastic resin film from becoming unnecessarily thick.
[0067] As will be described later, the thermoplastic resin film of the present invention is preferably an interlayer film for laminated glass used between a pair of transparent substrates in laminated glass. Also, as described above, the thermoplastic resin film of the present invention has a single-layer structure or a multilayer structure. When the thermoplastic resin film of the present invention has a multilayer structure, some of the layers may be the thermoplastic resin layer (A), or all of the layers may be the thermoplastic resin layer (A). Further, in the case of a multilayer structure, it is sufficient that either one of the outermost layers is the thermoplastic resin layer (A), but it is preferable that both outermost layers are the thermoplastic resin layer (A). When both outermost layers are the thermoplastic resin layer (A), the adhesive force to other members such as glass can be easily adjusted to an appropriate range by a metal salt of an organic acid having 5 or more carbon atoms in total. Also, when crimping to other members such as glass, it becomes easier to suppress the remaining air and the foaming of the peripheral portion. On the other hand, in the case of a single-layer structure, the thermoplastic resin film may preferably consist of a single layer of the above thermoplastic resin layer (A).
[0068] For example, in the case of a two-layer structure, the thermoplastic resin film may have either one of them as the thermoplastic resin layer (A), but it is preferable that both are the thermoplastic resin layer (A). Also, when the thermoplastic resin film has a three-layer structure having two outermost layers and a middle layer, either one of the two outermost layers may be the thermoplastic resin layer (A), but it is preferable that both outermost layers are the thermoplastic resin layer (A). In this case, the middle layer may be composed of the thermoplastic resin layer (A), or may be composed of other than the thermoplastic resin layer (A). Further, the thermoplastic resin film may have two outermost layers and two or more intermediate layers, and may have a structure of four or more layers. In this case, either one of the two outermost layers may be the thermoplastic resin layer (A), but it is preferable that both are the thermoplastic resin layer (A). Also, each intermediate layer may be composed of the thermoplastic resin layer (A), or may be composed of other than the thermoplastic resin layer (A). Also, when the thermoplastic resin film of the present invention has a plurality of layers of the thermoplastic resin layer (A), the thermoplastic resin layers (A) may have the same configuration or different configurations. For example, in the plurality of thermoplastic resin layers (A), the types of the thermoplastic resins constituting them and their contents may be the same as each other or different from each other.
[0069] Also, when the thermoplastic resin film has a layer other than the thermoplastic resin layer (A), such a layer may be a thermoplastic resin layer other than the thermoplastic resin layer (A). The type of the thermoplastic resin used for the thermoplastic resin layer other than the thermoplastic resin layer (A) is not particularly limited, but those listed as the thermoplastic resin (a) that can be used for the above thermoplastic resin layer (A) may be appropriately selected and used, and the types of resins that can be preferably used are the same. Therefore, it is particularly preferable to use a polyvinyl acetal resin.
[0070] In the thermoplastic resin film, the thickness of each specific thermoplastic resin layer (A) is not particularly limited, but for example, it is 50 μm or more and 1500 μm or less, preferably 100 μm or more and 1000 μm or less, more preferably 200 μm or more and 900 μm or less. By having a thickness of a certain level or more, the thermoplastic resin layer (A) can easily suppress the remaining air during pressure bonding. Also, by setting the thickness to a certain level or less, it is possible to prevent the thermoplastic resin film from becoming thicker than necessary.
[0071] In the thermoplastic resin film, the thermoplastic resin layer (A) is not particularly limited, but it preferably occupies a certain proportion or more of the total thickness of the thermoplastic resin film. Specifically, the total thickness of the thermoplastic resin layer (A) may be, for example, in a proportion of 0.1 or more and 1 or less with respect to the total thickness of the thermoplastic resin film, preferably 0.3 or more and 1 or less, more preferably 0.5 or more and 1 or less, and even more preferably 0.75 or more and 1 or less. By containing the thermoplastic resin layer (A) in a certain thickness ratio or more in the thermoplastic resin film, it becomes easier to suppress the residual air during crimping and the foaming of the peripheral portion.
[0072] The manufacturing method of the thermoplastic resin film is not particularly limited. In the case of a single-layer structure, the thermoplastic resin (a) is mixed with a metal salt of an organic acid, and a plasticizer and other additives that are blended as necessary to obtain a resin composition for forming the thermoplastic resin layer (A), and the resin composition may be obtained by extrusion molding, press molding, etc. In addition, in the case of a multilayer structure, a resin composition for forming each layer may be obtained, and each layer may be formed and laminated by extrusion molding, press molding, etc. At this time, when extrusion molding is adopted, coextrusion molding is preferable. Further, the thermoplastic resin film may have an uneven shape on one or both surfaces. The method for forming the uneven shape is not particularly limited, and examples thereof include a lip embossing method, an embossing roll method, and a calendar roll method.
[0073] <Laminate> The laminate of the present invention includes at least one of the above-described thermoplastic resin film, a functional layer, and a transparent substrate. By using the thermoplastic resin film having the above-described thermoplastic resin layer (A) in the laminate of the present invention, the thermoplastic resin film can be appropriately adhered to other members such as a functional layer and a transparent substrate without using an autoclave process under high-temperature and high-pressure conditions, so that its production becomes easy. In addition, it is possible to suppress the deactivation of the functional layer when the functional layer is incorporated into the laminate.
[0074] When the laminate of the present invention has a transparent substrate, the thermoplastic resin film is preferably disposed at a position in contact with the transparent substrate. Among them, it is more preferable that the thermoplastic resin layer (A) is disposed at a position in contact with the transparent substrate. The transparent substrate is preferably a glass plate described later, and more preferably inorganic glass. The thermoplastic resin film of the present invention can be adhered to the transparent substrate with an appropriate adhesive force by disposing the thermoplastic resin layer (A) at a position in contact with the transparent substrate, particularly a glass plate described later, and more preferably an inorganic glass plate.
[0075] In the laminate of the present invention, the functional layer is preferably disposed between a pair of thermoplastic resin films. When the functional layer is disposed between a pair of thermoplastic resin films, the functional layer can be easily incorporated into a laminate such as laminated glass.
[0076] [Functional layer] The functional layer used in the laminate of the present invention is not particularly limited as long as it is a layer having a predetermined function. As the functional layer used in the laminate of the present invention, for example, a functional film can be used. The functional film may be a dimming film, a display element film, or an optical film such as a polarizing film, a retardation film, or an antireflection film. Further, a solar cell element can also be used as the functional layer.
[0077] Among the above, the functional film is preferably a film provided with electronic components such as a dimming film and a display element film. A film provided with electronic components is likely to have its function deteriorated or deactivated when integrated by an autoclave under high temperature and high pressure conditions. However, according to the present invention, since it is not necessary to press-bond the thermoplastic resin film to the functional layer in the autoclave process under high temperature and high pressure conditions, the functional layer can be incorporated into the laminate without deactivating the functional layer. Therefore, even a film provided with electronic components can be incorporated into the laminate so that it can be practically used. In addition, a dimming film, a display element film, or a solar cell element can provide highly value-added window glass when a laminate having any of these is incorporated into various window glasses. Therefore, in the present invention, it is desirable to use any of these as a functional layer.
[0078] A dimming film is a film-like member having a dimming element. Specifically, the dimming element is preferably a dimming film including two resin films and a dimming layer disposed between the two resin films. Therefore, the adhesion surface of the dimming film with the thermoplastic resin film becomes a resin material, and the adhesion strength to the thermoplastic resin film tends to be high. The resin film used for the dimming element is not particularly limited, and examples include polyester resin films such as PET films and PEN films, (meth)acrylic resin films, TAC films, PES resin films, and polyimide resin films. Among these, from the viewpoint of handleability and the like, a polyester resin film is preferable, and among them, a PET film is more preferable. Further, a conductive layer constituting an electrode is provided on the surface on the dimming layer side of each of the two resin films.
[0079] The dimming layer is one in which the visible light transmittance changes by switching the application and non-application of voltage between the conductive layers of the two resin films. The dimming layer is composed of a liquid crystal layer such as a polymer dispersed liquid crystal (PDLC), and the dimming film may be a PDLC film. Further, the dimming film may be an SPD (Suspended Particle Device) film, an electrochromic film, an electrophoretic film device, a GHLC (Guest Host Liquid Crystal) film, or the like. Therefore, the dimming layer may be an SPD layer including a resin matrix and a light adjustment suspension dispersed in the resin matrix, or may be an electrochromic material layer. Further, it may be an electrophoretic layer including electrophoretic particles and a dispersant for dispersing the electrophoretic particles. Furthermore, the dimming layer may be a GHLC layer made of a G-H (guest-host) material by dye doping, or the like.
[0080] The display element film is a film-like member provided with a display element. Examples of the display element film include those comprising a resin film and a display element mounted on the resin film. The display element film may also be one having a pair of resin films with a display element provided therebetween. According to such a configuration, when the display element film is disposed between a pair of thermoplastic resin films and incorporated into a laminate, it can be adhered to the thermoplastic resin film with high adhesiveness. Note that as the resin film used for the display element film, the resin films listed in the light control film can be appropriately selected and used. Also, in the display element film, the resin film may be provided with a conductive layer constituting an electrode on the surface on the display element side. Examples of the display element include an organic EL element, an LED display, a segment display, etc., among which an organic EL element is preferable.
[0081] Note that the functional film having an electronic component is not limited to the above-described display element film and light control film, and may be other functional films. However, the electronic component may be mounted on the resin film in the same manner as the display element film and the light control film, but an aspect in which the electronic component is disposed between a pair of resin films is preferable.
[0082] Also, by using a solar cell element in the functional layer of the laminate, for example, a laminated glass for building-integrated photovoltaics (BIPV) can be provided. The solar cell element is not particularly limited, and may be a solar cell element used for building-integrated power generation equipment (BIPV). For example, crystalline or thin-film silicon-based solar cell elements; compound semiconductor-based solar cell elements such as CIS, CIGS, CdTe, GaAs, etc.; organic-based solar cell elements such as dye-sensitized, organic thin-film, perovskite, etc. can be mentioned.
[0083] The thickness of the functional layer is not particularly limited, but is preferably 10 μm or more and 1500 μm or less, more preferably 50 μm or more and 1000 μm or less, and still more preferably 100 μm or more and 800 μm or less. Note that although the thickness of the functional layer may vary depending on the position, when the thickness changes, it means the maximum thickness.
[0084] [Transparent substrate] Examples of the transparent substrate used in the laminate of the present invention include a resin film and a glass plate, but a glass plate is preferable. The glass plate may be either inorganic glass or organic glass, but inorganic glass is preferable. The inorganic glass is not particularly limited, and examples thereof include clear glass, float plate glass, tempered glass, colored glass, polished plate glass, patterned plate glass, wired glass, wired patterned glass, ultraviolet absorbing plate glass, infrared reflecting plate glass, infrared absorbing plate glass, and green glass. As the organic glass, what is generally called resin glass is used, and examples thereof include (meth)acrylic plates such as polycarbonate plates and polymethyl methacrylate plates, acrylonitrile styrene copolymer plates, acrylonitrile butadiene styrene copolymer plates, and polyester plates such as polyethylene terephthalate plates, fluororesin plates, polyvinyl chloride plates, chlorinated polyvinyl chloride plates, polypropylene plates, polystyrene plates, polysulfone plates, epoxy resin plates, phenolic resin plates, unsaturated polyester resin plates, polyimide resin plates, and other various organic glass plates. The organic resin plate may be appropriately subjected to surface treatment or the like.
[0085] The thickness of each glass plate used as the transparent substrate is not particularly limited, but is, for example, about 0.1 to 15 mm, preferably 0.5 to 5 mm. The thicknesses of the respective glass plates may be the same as or different from each other.
[0086] The transparent substrate may be composed of a single glass plate or may be a glass plate to which other members are attached. It is preferable that a functional member is attached to the glass plate to impart various functions. The other member may be a member constituting, for example, an electronic device, an optical member, etc., but is preferably a member constituting a display device. The display device may be, for example, a liquid crystal display device, an organic EL display device, an LED display device, a segment display device, etc. Among these, a liquid crystal display device is preferable as the display device.
[0087] The display device may be, for example, a display panel in which a glass plate is used as a substrate and a display layer such as a liquid crystal layer or an organic EL layer, a light-emitting element, etc. are provided on the substrate. It is preferable to use the glass plate serving as the substrate of the display panel as the transparent base material. In addition, a functional layer such as the above-described functional film, an electrode, a conductive layer constituting a sensor, etc., an antireflection layer, a hard coat layer, etc. may be laminated on the glass plate. However, the transparent base material may be a glass plate on which such a functional film or functional layer is laminated. Therefore, the contact surface with the thermoplastic resin film, on which the thermoplastic resin film is directly laminated, may be the glass plate itself or the surface of the functional film or functional layer.
[0088] The laminate is not particularly limited, but preferably has a structure having the first and second transparent base materials and at least one of the thermoplastic resin films of the present invention provided therebetween. In this case, it is more preferable that both the first and second transparent base materials are glass plates and the laminate is laminated glass. In laminated glass, the first and second transparent base materials may be made of the same kind of material as each other or different materials. For example, one may be inorganic glass and the other may be organic glass. However, it is preferable that both the first and second transparent base materials are inorganic glass or organic glass, and it is more preferable that both the first and second transparent base materials are inorganic glass.
[0089] Hereinafter, the layer structure in the case where the laminate is laminated glass will be described in more detail with reference to the drawings. As shown in FIG. 1, in the first embodiment of the present invention, the laminated glass 1A is a laminate in which one thermoplastic resin film 10 is provided between first and second transparent substrates 20 and 30 which are glass plates. In the laminated glass 1A, the thermoplastic resin film 10 is adhered to both the first and second transparent substrates 20 and 30 to bond them together.
[0090] In the first embodiment, the thermoplastic resin layer (A) of the thermoplastic resin film 10 may be composed of a single layer of the thermoplastic resin layer (A) or may have a multilayer structure. When it has a multilayer structure, it is preferable to have the thermoplastic resin layer (A) in both outermost layers. With the above configuration, in either the single-layer structure or the multilayer structure, the thermoplastic resin layer (A) is arranged at the position where it contacts the glass plate, so that it can be adhered to the glass plate with an appropriate adhesive force. Also, the laminate can be easily manufactured by low-temperature fusion.
[0091] In the first embodiment, at least one of the first and second transparent substrates 20 and 30 is preferably one to which other members are attached as described above. Specifically, functional members such as electronic devices such as display devices and optical members may be attached, or those with the above-described functional layers laminated may be used. Even if a functional member or a functional layer is provided on either one of the first and second transparent substrates 20 and 30 in the laminated glass 1A according to the first embodiment, it can be pressure-bonded and integrated without going through an autoclave process under high-temperature and high-pressure conditions. Thus, it is possible to prevent the functional member or the functional layer attached to the laminated glass 1A from deteriorating or deactivating.
[0092] Also, as another preferred embodiment, the laminated glass may be one in which a plurality of thermoplastic resin films are provided between the first and second transparent substrates. An embodiment of the laminated glass in the case where a plurality of thermoplastic resin films are provided is shown in FIG. 2 as the second embodiment. As shown in FIG. 2, in the laminated glass 1B according to the second embodiment, a pair of thermoplastic resin films 10 are provided between the first and second transparent substrates 20 and 30, and a functional layer 40 is further provided between the pair of thermoplastic resin films 10. That is, in the laminated glass 1B according to the second embodiment, a laminated intermediate body 50 in which the functional layer 40 is provided between a pair of thermoplastic resin layers 10 is provided between the first and second transparent substrates 20 and 30.
[0093] In the laminated glass 1B, one thermoplastic resin film 10 is adhered to both the first transparent substrate 20 and the functional layer 40 to join them, and the other thermoplastic resin film 10 is adhered to both the second transparent substrate 30 and the functional layer 40 to join them. Thereby, the first and second transparent substrates 20 and 30 are integrated by the thermoplastic resin film 10 together with the functional layer 40.
[0094] In the second embodiment, the thermoplastic resin film 10 may be composed of a single layer of the thermoplastic resin layer (A) or may have a multilayer structure. In the case of a multilayer structure, the thermoplastic resin layer (A) in each thermoplastic resin film 10 is preferably arranged at a position in contact with each of the transparent members 20 and 30. With the above configuration, in either the single-layer structure or the multilayer structure, the thermoplastic resin layer (A) is arranged at a position in contact with the transparent substrate that is a glass plate, so that it is possible to adhere to the glass plate with an appropriate adhesive force. In addition, the laminate can be easily manufactured by low-temperature fusion. Further, in the second embodiment, the thermoplastic resin film 10 having a multilayer structure may have the thermoplastic resin layer (A) on both outermost layers. In that case, in each thermoplastic resin film 10, the thermoplastic resin layer (A) comes into contact with the transparent member and the functional layer. Similarly, even when each thermoplastic resin film 10 is composed of a single-layer thermoplastic resin layer (A), the thermoplastic resin layer (A) comes into contact with the transparent member and the functional layer. Therefore, the laminated glass 1B is easily adhered to the functional layer as well as the transparent member with an appropriate adhesive force.
[0095] In the second embodiment, a mode is shown in which two thermoplastic resin films 10 are provided on the laminated glass 10B and one functional layer 40 is provided. However, three or more thermoplastic resin films may be provided on the laminated glass and two or more functional layers may be provided. In this case, in the laminated glass, the thermoplastic resin film and the functional layer may be alternately arranged. And thermoplastic resin films may be arranged at the positions closest to the first and second transparent substrates. For example, when three thermoplastic resin films 10 are provided and two functional layers are provided, they may be arranged in the order of the first transparent substrate / thermoplastic resin film / functional layer / thermoplastic resin film / functional layer / thermoplastic resin film / second transparent substrate.
[0096] Even when three or more thermoplastic resin films are provided, the thermoplastic resin film arranged at the position closest to the transparent substrate may have a single-layer structure or a multilayer structure with a thermoplastic resin layer (A) arranged at the position in contact with the transparent substrate. With such a configuration, in the laminated glass, the thermoplastic resin film can be adhered to the transparent substrate, which is a glass plate, with an appropriate adhesive force. Also, the laminate can be easily manufactured by low-temperature fusion. Furthermore, when the thermoplastic resin film arranged at the position closest to the transparent substrate has a multilayer structure, the thermoplastic resin layer (A) may be arranged on both outermost layers. Similarly, the thermoplastic resin films other than the thermoplastic resin film arranged at the position closest to the transparent substrate may be of a single-layer structure or a multilayer structure with the thermoplastic resin layer (A) arranged on both outermost layers, whereby the thermoplastic resin film can be easily adhered to the functional layer etc. with an appropriate adhesive force.
[0097] In the laminate, when a plurality of thermoplastic resin films are provided, a functional layer may not be provided, and only the thermoplastic resin films may be provided between a pair of transparent substrates. Further, in the laminate, when a plurality of thermoplastic resin films are provided, the configurations of the respective thermoplastic resin films may be the same or different. Furthermore, in the above description, when a plurality of thermoplastic resin films are provided, the description is based on the premise that all the thermoplastic resin films are the thermoplastic resin films of the present invention, but only some of the thermoplastic resin films may be the thermoplastic resin films of the present invention.
[0098] (Method for manufacturing laminate) The laminate of the present invention can be manufactured, for example, by preparing a thermoplastic resin film and pressing and bonding the prepared thermoplastic resin film to each member such as a functional layer or a transparent substrate. Further, when the thermoplastic resin film is disposed between two members, it is preferable to dispose the thermoplastic resin film between the two members and press-bond them to bond them. For example, in the first embodiment described above, the laminate of the present invention can be manufactured by stacking a first transparent substrate, a thermoplastic resin film, and a second transparent substrate in this order and pressing and bonding them. Further, in the second embodiment, it can be manufactured by stacking a first transparent substrate, a thermoplastic resin film, a functional layer, a thermoplastic resin film, and a second transparent substrate in this order and pressing and bonding them.
[0099] However, for the laminate, a part of the laminate may be pre-pressed and integrated in advance to obtain a laminate intermediate, and then the laminate intermediate may be pressed and bonded to another member to obtain the laminate. For example, as described above, for the laminate having the first and second transparent substrates, the laminate may be obtained by pressing and bonding a pair of transparent substrates and a laminate intermediate disposed between the pair of transparent substrates. Here, the laminated intermediate preferably includes at least one thermoplastic resin film, but preferably includes at least two thermoplastic resin films and a functional layer, and both surfaces of the laminated intermediate are each composed of a thermoplastic resin film. For example, a thermoplastic resin film, a functional layer, and a thermoplastic resin film are pressure-bonded to obtain a laminated intermediate body, and then the laminated intermediate body is disposed between a pair of transparent substrates and then pressure-bonded and bonded to obtain a laminate.
[0100] Also, as described above, in the laminate, a functional member may be attached to at least one of the first and second transparent substrates, but the functional member is preferably attached to the transparent substrate before being integrated into the laminate. Therefore, in the above manufacturing method, at least one of the first and second transparent substrates may be prepared as a transparent substrate to which a functional member is attached.
[0101] In this manufacturing method, as described above, a laminate may be obtained by pressure-bonding and bonding a plurality of layers. Among them, it is preferable to dispose one or a plurality of layers including a thermoplastic resin film or a laminated intermediate between the first transparent substrate and the second transparent substrate, and pressure-bond and bond them to integrate them to obtain a laminate such as laminated glass. The bonding for obtaining the above laminate may be performed by a vacuum bag, may be performed by an autoclave under low-temperature conditions, or may be performed by other pressing machines. Among these, it is preferable to perform it by a vacuum bag. Further, before performing the above bonding, temporary pressure-bonding may be performed using a rubber roll or the like.
[0102] In this manufacturing method, the above bonding is preferably performed under low-temperature conditions. Specifically, it is preferably pressure-bonded at a temperature of 110°C or lower. Further, the above bonding is preferably performed at low temperature and low pressure. Specifically, it is preferably pressure-bonded at a temperature of 110°C or lower and a pressure of 1.0 MPa or lower. By performing the bonding under such low-temperature and low-pressure conditions, it is possible to prevent the functional layer and the functional members attached to the first and second transparent substrates from deteriorating or deactivating.
[0103] When performing the lamination, the temperature is preferably 110°C or lower from the viewpoint of more surely preventing deterioration and deactivation of the functional member. However, from the viewpoint of appropriately adhering between the layers while preventing generation and foaming of residual air, it is preferably 60°C or higher, more preferably 70°C or higher. Also, the pressure when performing the lamination is preferably 1.2 MPa or lower from the viewpoint of more surely preventing deterioration and deactivation of the functional member. When performing under negative pressure as in the case of using a vacuum back, for example, it may be 0.095 MPa or lower, preferably 0.08 MPa or lower, and more preferably 0.06 MPa or lower. The pressure when performing the lamination is not particularly limited with respect to the lower limit value. However, for example, when performing under pressure such as in an autoclave, it is preferably 0.5 MPa or higher, more preferably 0.7 MPa or higher. When performing under negative pressure as in the case of using a vacuum back, it is preferably 0.001 MPa or higher, more preferably 0.005 MPa or higher. Also, the time for performing the lamination at the above temperature and pressure is not particularly limited, but is, for example, 5 to 120 minutes, preferably 10 to 90 minutes.
[0104] The thermoplastic resin film and laminate of the present invention are not particularly limited and can be used for various applications. However, as described above, they can be suitably used for laminated glass. The thermoplastic resin film and laminate of the present invention are used for window glasses of various vehicles such as automobiles, trains, ships, airplanes, etc., or various buildings such as buildings, condominiums, single-family houses, halls, gymnasiums, etc., or machine tools such as cutting and polishing, construction machinery such as shovels and cranes, etc., or partitions inside various vehicles and various buildings. Among them, vehicle applications such as automobiles are preferred, and it is preferably used for window glasses for vehicles. Further, when the laminate of the present invention constitutes a display device with a transparent substrate, for example, it may be used for various display applications. As display applications, the above-described window glass or partition may be used as a display. Further, the laminate may be used as a cover glass for various displays, for example, it may be applied to in-vehicle displays and the like.
Examples
[0105] The present invention will be described in more detail with reference to examples, but the present invention is not limited by these examples. The measurement methods and evaluation methods for each physical property value in the present invention are as follows.
[0106] <Amount of thickness change during compression creep test> According to the method described in the specification, the thermoplastic resin layers of each example and comparative example were cut out to prepare test samples with a diameter of 8 mm. Using the prepared test samples, the amount of thickness change was determined according to the method described in the specification.
[0107] <Molecular weight (Mw, Mn)> The thermoplastic resin used in each example and comparative example was dissolved at a concentration of 0.05% by mass in an N-methyl-2-pyrrolidone solution containing lithium bromide so as to be 10 mM, filtered using a syringe filter (Merck, Millex-LH 0.45 μm), and then the molecular weight was measured using gel permeation chromatography (Waters, e2690). The number average molecular weight (Mn) and the weight average molecular weight (Mw) were calculated using a molecular weight calibration curve prepared with a monodisperse polystyrene standard sample, and the molecular weight distribution (Mw / Mn) was also determined. Further, Shodex GPC KF-806L (manufactured by Showa Denko KK) was used as the column, and an N-methyl-2-pyrrolidone solution containing lithium bromide so as to be 10 mM was used as the eluent.
[0108] <Amount of hydroxyl groups, degree of acetylation, degree of acetalization> ·Measurement of the content (mass%) of ethylene groups to which hydroxyl groups are bonded 0.4 g of the sample was accurately weighed into a 200 mL conical flask with a stopper. After adding 10.0 mL of a pyridine - acetic anhydride mixed solution to the sample, the sample was dissolved in the pyridine - acetic anhydride mixed solution by heating on a water bath at a bath temperature of 90 °C and irradiating with ultrasonic waves. A reflux condenser was attached to the conical flask, and the mixture was heated under reflux on the water bath for 120 minutes. After the reaction, 25 mL of pyridine was used to wash the condenser, and the sample solution after the reaction was cooled to room temperature. To the cooled sample solution, 20 mL of 1,2 - dichloroethane was added, and after shaking, 50 mL of water was further added, shaken, and left standing at room temperature for 30 minutes. Then, potentiometric titration was performed on the sample solution with a 0.5 mol / L (0.5 N) sodium hydroxide solution. An empty test was carried out in the same manner except that no sample was used, and based on the following formula, the ethylene group content (mass %) in which the hydroxyl group is bonded in the sample was determined.
Equation
[0109] ·Measurement of the ethylene group content (mass %) in which an acetyl group is bonded 0.4 g of the sample was accurately weighed into a 200 mL conical flask with a stopper. After adding 100.0 mL of ethanol to the sample, the sample was dissolved in ethanol by heating on a water bath at a bath temperature of 90 °C and irradiating with ultrasonic waves. While shaking the conical flask, 10.0 mL of 0.2 mol / L (0.2 N) sodium hydroxide was added. A reflux condenser was attached to the conical flask, and the mixture was heated under reflux in the water bath for 60 minutes. After the reaction, 25 mL of ethanol was used to wash the condenser, and the sample solution after the reaction was cooled to room temperature. To the cooled sample solution, 10.0 mL of 0.2 mol / L (0.2 N) hydrochloric acid was added, shaken well, and left at room temperature for 30 minutes. Then, potentiometric titration was performed on the sample solution with a 0.1 mol / L (0.1 N) sodium hydroxide solution. An empty test was carried out in the same manner except that no sample was used, and based on the following formula, the ethylene group content (mass %) to which the acetyl group was bonded in the sample was determined.
Number
[0110] ·Measurement of ethylene group content (mass %) to which the butyral group is bonded Based on the following formula, the ethylene group content (mass %) to which the butyral group is bonded was determined from the ethylene group content (mass %) to which the hydroxyl group is bonded and the ethylene group content (mass %) to which the acetyl group is bonded obtained by the method described above.
Number
[0111] [Preparation of laminated glass] The obtained intermediate film was sandwiched between two clear glasses with a thickness of 2.5 mm to obtain a laminate. The obtained laminate was temporarily pressure-bonded using a heating roll at 170°C. The temporarily pressure-bonded laminate was pressure-bonded for 20 minutes under the conditions of 135°C and a pressure of 1.2 MPa in an autoclave to obtain laminated glass.
[0112] [Δhaze] Using the thermoplastic resin films obtained in each example and comparative example, laminated glass was prepared and stored in an environment at 100°C for 1000 hours or 2000 hours. The haze values of the laminated glass before storage and after 1000 hours or 2000 hours of storage were measured, and the value obtained by subtracting the haze value before storage from the haze value after storage was determined as Δhaze. The haze value was determined by measuring from one side of the laminated glass using a HAZE METER "HM-150N" manufactured by Murakami Color Co., Ltd. in accordance with JIS K6714.
[0113] [Adhesiveness] The laminated glass produced using the thermoplastic resin films obtained in the examples and comparative examples was allowed to stand in an environment at a temperature of -18°C ± 0.6°C for 16 hours. The central part (a portion of 150 mm in length × 150 mm in width) of this laminated glass was struck with a hammer having a head weight of 0.45 kg until the glass particles had a size of 6 mm or less, and the exposure degree of the film after the glass was partially peeled off was measured, and the Pannel value was determined according to Table 1. The average value of the six measurement values was adopted as the Pannel value. When the Pannel value was 2 to 7, it was evaluated as "A" assuming that the adhesive force was properly adjusted, and when the Pannel value was 1 or less or 8 or more, it was evaluated as "B" assuming that the adhesive force was not properly adjusted.
[0114]
Table 1
[0115] The thermoplastic resins used in the examples and comparative examples were prepared as follows. (Resin 1) Into a reactor equipped with a stirrer, 1800 ml of ion-exchanged water and 200 g of polyvinyl alcohol (average degree of polymerization 1700, degree of saponification 99 mol%) were placed, and heated and dissolved with stirring to obtain a polyvinyl alcohol solution. Next, 30% hydrochloric acid was added to this solution as a catalyst so that the hydrochloric acid concentration became 0.2% by mass. After adjusting the temperature to 15°C, n-butylaldehyde was added with stirring so that it became 10 mol%. Then, when n-butylaldehyde was added so that it became 60 mol%, white particulate polyvinyl butyral resin precipitated. Ten minutes after the precipitation, 30% hydrochloric acid was added so that the hydrochloric acid concentration became 1.8% by mass, and then the temperature was raised to 53°C and aged at a aging temperature of 53°C for 2 hours. Next, the solution was cooled, neutralized, and then the polyvinyl butyral resin was washed with water and dried to obtain Resin 1 (polyvinyl butyral resin, hydroxyl group amount 30.8 mol%, degree of acetalization 68.4 mol%, degree of acetylation 0.8 mol%, degree of polymerization 1700, weight average molecular weight 291,000, dispersity (Mw / Mn: 1.81)).
[0116] The plasticizers used in the examples and comparative examples are as follows. 3GO: Triethylene glycol - di - 2 - ethylhexanoate
[0117] (Example 1) To 100 parts by mass of Resin 1, 40 parts by mass of a plasticizer (triethylene glycol - di - 2 - ethylhexanoate: 3GO) and magnesium 2 - ethylbutyrate were mixed to obtain a resin composition. Note that magnesium 2 - ethylbutyrate was blended so that the magnesium content was 70 ppm. Using the obtained resin composition, a thermoplastic resin film having a single - layer structure with a thickness of 800 μm in film form was produced using a hydraulic press and a spacer with a thickness of 800 μm.
[0118] (Example 2) It was carried out in the same manner as in Example 1, except that the blending amount of magnesium 2 - ethylbutyrate was adjusted so that the magnesium content was 40 ppm as shown in Table 2.
[0119] (Comparative Examples 1 and 2) It was carried out in the same manner as in Example 1, except that magnesium acetate was used instead of magnesium 2 - ethylbutyrate and the blending amount of magnesium acetate was adjusted so that the magnesium content was as described in Table 2.
[0120] (Comparative Example 3) It was carried out in the same manner as in Example 1, except that magnesium propionate was used instead of magnesium 2 - ethylbutyrate and the blending amount of magnesium propionate was adjusted so that the magnesium content was as described in Table 2.
[0121] (Comparative Example 4) It was carried out in the same manner as in Example 1, except that magnesium 2 - methylpropionate was used instead of magnesium 2 - ethylbutyrate and the blending amount of magnesium 2 - methylpropionate was adjusted so that the magnesium content was as described in Table 2.
[0122]
Table 2
[0123] In the above Examples 1 and 2, the amount of thickness change during compression creep was 80 μm or more. While using the soft thermoplastic resin layer (A) suitable for low-temperature fusion, since the total carbon number of the organic acid in the metal salt of the organic acid was 5 or more, not only when the laminated glass was left at a high temperature for 1000 hours, but also when left for 2000 hours, Δhaze was low and clouding did not occur. On the other hand, in Comparative Examples 2 and 3, since the total carbon number of the organic acid in the metal salt of the organic acid used as the adhesion adjuster was less than 5, when the laminated glass was left at a high temperature for 1000 hours, Δhaze increased and clouding occurred. In Comparative Example 1, even though the total carbon number of the organic acid in the metal salt of the organic acid was less than 5, clouding did not occur. However, since the content of the metal salt of the organic acid was small, the adhesion of the thermoplastic resin film could not be appropriately adjusted by the metal salt of the organic acid.
Explanation of Reference Numerals
[0124] 1A, 2B Laminated glass 10 Thermoplastic resin film 20 First transparent substrate 30 Second transparent substrate 40 Functional layer 50 Laminated intermediate
Claims
1. A thermoplastic resin film having a single-layer structure or a multilayer structure, comprising at least a thermoplastic resin layer (A) containing a thermoplastic resin, when the thermoplastic resin film has a multilayer structure, at least one outermost layer is the thermoplastic resin layer (A), the thermoplastic resin layer (A) has a thickness change amount of 80 μm or more when compressed by a compression creep test performed under the following conditions, and is a thermoplastic resin film containing a metal salt of an organic acid having a total carbon number of 5 or more. (Compression creep test conditions) A test sample having a diameter of 8 mm and a thickness of 700 to 900 μm prepared from the thermoplastic resin layer (A) is compressed for 5 minutes under the conditions of a load of 410 g and a temperature of 30 °C, and then the thickness (T1) of the test sample is measured. Then, while maintaining a load of 410 g, the temperature is raised from 30 °C to 90 °C at a heating rate of 6 °C / min. And after compressing for 5 minutes under the conditions of a load of 410 g and a temperature of 90 °C, the thickness (T2) of the test sample is measured. The absolute value of the difference between the thickness (T1) and the thickness (T2) of the test sample is taken as the thickness change amount.
2. The thermoplastic resin film according to claim 1, wherein the carbon chain of the organic acid in the metal salt has a branched chain, and the carbon number of the main chain of the carbon chain is 4 or more.
3. The thermoplastic resin film according to claim 1, wherein the carbon chain of the organic acid in the metal salt has a branched chain, and the carbon number of the branched chain is 1 or more.
4. The thermoplastic resin film according to claim 1, wherein in the thermoplastic resin layer (A), the content of the metal contained in the metal salt is 40 ppm or more.
5. The thermoplastic resin film according to claim 1, wherein the thermoplastic resin layer (A) does not contain a metal salt of an organic acid having a total carbon number of 1 or more and 4 or less, or contains a metal salt of an organic acid having a total carbon number of 1 or more and 4 or less in an amount of less than 40 ppm by metal amount.
6. The thermoplastic resin film according to claim 1, wherein the thermoplastic resin is a polyvinyl acetal resin.
7. The thermoplastic resin film according to claim 6, wherein the polyvinyl acetal resin is a polyvinyl acetal resin aged at 30°C or higher and 65°C or lower for 75 minutes or longer and 180 minutes or shorter.
8. The thermoplastic resin film according to any one of claims 1 to 7, which is an interlayer film for laminated glass.
9. A laminate comprising the thermoplastic resin film according to any one of claims 1 to 7 and at least one of a functional layer and a transparent substrate.
10. A laminated glass comprising the thermoplastic resin film according to any one of claims 1 to 7 and a pair of glass members, wherein the thermoplastic resin film is disposed between the pair of glass members.
Citation Information
Patent Citations
Interlayer for laminated glass and laminated glass using the same
JP1998273344A
Sandwich glass and sandwich glass structure
JP2001039743A
Interlayer containing stabilized tungsten oxide agent
JP2010535695A
Interlayer film for laminated glass and laminated glass
JP2023026450A
Heat-ray-shielding film, heat-ray-shielding transparent substrate, heat-ray-shielding resin sheet material, vehicle, and building
WO2014163119A1